Administering AEC professionals’ project delivery cross-culture productivity: Malaysia vs United Kingdom - Maszura Abdul Ghafar (Penerbit Universiti Kebangsaan Malaysia, 2024)
Borderless world is transforming construction professionals on how to communicate and work across the globe. Many missed communication and different work culture could result in many variation orders and time wastage in construction. This paper looks to discuss the mixed research methodology results on how to administer architect, engineer and contractor (AEC) professionals’ cross-work culture productivity during building deployment. 34 participants were selected for semi-structured interviews and participatory observations were conducted in two multidisciplinary teams of architect, engineer, and contractor from the United Kingdom (UK) and the Malaysia firms for six months. Then, SimVision® simulations were use as the Cognitive Organizational Theory (COT) protocols based on structural system and project dexterity parameters. Statistics corroborations were then conducted to obtain generalization and reliability. The case study results showed that the UK and the Malaysian team have similarities in operating nature of building deployment and differences in practice and value preferences when delivering a project, whilst model MMsRwB is the ideal for replicating UK’s project productivity efficiency. The findings could guide international construction professionals or teams from developed and developing countries to joint venture in their country successfully especially for Malaysian context. The paper would firstly discuss the literature, secondly describe the mixed method methodology and then present the expected result. The paper recommends future research on formalizing communication system for AEC professionals through integrating Malaysian AEC transdisciplinary global practice in a design studio education program.